1997
DOI: 10.1111/j.1600-0773.1997.tb00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Influences of Different Adrenoceptors on Baclofen‐Induced Antinociception in Mice

Abstract: In the present study, the effects of adrenoceptor agonists and antagonists on baclofen-induced antinociception was investigated. Intraperitoneal administration of different doses of baclofen (2.5, 5 and 10 mg/kg) induced antinociception in the tail-flick test. The response was dose-dependent. The a2-adrenoceptor agonist, clonidine, increased, while the a'-adrenoceptor agonist, phenylephrine, decreased the baclofen response. In reserpine-treated animals, a,-adrenoceptor, clonidine, induced antinociception and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…(1986a , b) studied different alpha‐1 and alpha‐2 adrenoceptor agonists and antagonists in rats and dogs and concluded that antinociception may be mediated by either alpha‐1 or alpha‐2 adrenoceptors whereas sedation is predominantly mediated by alpha‐2‐adrenoceptors. In another study with mice, however, alpha‐2 adrenoceptor stimulation increased, while alpha‐1‐adrenoceptor stimulation decreased baclofen‐induced antinociception ( Sabetkasai et al ., 1997 ). These two conclusions may appear to be contradictory as far as the role of alpha‐1‐adrenoceptors in antinociception is concerned but consideration should be given to the fact that different species, different drugs and different tests were used.…”
Section: Discussionmentioning
confidence: 97%
“…(1986a , b) studied different alpha‐1 and alpha‐2 adrenoceptor agonists and antagonists in rats and dogs and concluded that antinociception may be mediated by either alpha‐1 or alpha‐2 adrenoceptors whereas sedation is predominantly mediated by alpha‐2‐adrenoceptors. In another study with mice, however, alpha‐2 adrenoceptor stimulation increased, while alpha‐1‐adrenoceptor stimulation decreased baclofen‐induced antinociception ( Sabetkasai et al ., 1997 ). These two conclusions may appear to be contradictory as far as the role of alpha‐1‐adrenoceptors in antinociception is concerned but consideration should be given to the fact that different species, different drugs and different tests were used.…”
Section: Discussionmentioning
confidence: 97%
“…However, given that there was no effect of propranolol when administered before the test of fear expression, which also depends on the LA, it appears that propranolol does not inactivate or disrupt the LA. One more explanation might be that propranolol attenuated footshock sensitivity, but in contrast to causing antinociception, propranolol has previously been shown to inhibit antinociception in the tail-flick test produced by systemic baclofen (Sabetkasai et al, 1997) or amygdala stimulation (Oliveira and Prado, 1998), and propranolol treatments that impair inhibitory avoidance retention are reported to have no effect on footshock sensitivity (Nielson et al, 1999). These findings suggest that the current effect on freezing during fear conditioning was not caused by reduced shock sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The drug is known to interact with a variety of neurotransmitter systems. The noradrenergic (Sawynok 1983(Sawynok & 1987Sabetkasai et al 1997), dopaminergic (Zarrindast & Moghadampour 199 1) and adenosine systems (Sabetkasai & Zarrindast 1993) are known to influence baclofen antinociception. It has also been suggested that muscarinic mechanisms are involved in this response, as antinociception is reduced by the muscarinic receptor antagonists, atropine and scopolamine (Bartolini et al 1982;Kendall et al 1982;Tamayo et al 1988;Waught et al 1985) and increased by the choline esterase inhibitor, physostigmine (Tamayo et al 1988).…”
Section: Discussionmentioning
confidence: 99%